Pentingnya Stepping the 5 Stairs â€œAâ€ Teknik Untuk Anak-Anak Pesisir yang Belajar Grammar - Satria Agust; Gatot Subroto; Muhammad Candra (Jurnal Anugerah, 2019)
The English learning experience especially Grammar should be done in a fun way and make the language learners master the concept well. The importance of mastering Grammar well facilitates language learners to construct English sentences from various tenses. Coastal language learners have not been given good grammar understanding and do not have enough time to learn grammar in schools. To master Grammar, Stepping the 5 Stairs "A" technique offers fun grammar learning. There are already many techniques offered. However, the existing techniques do not accommodate the characteristics of the language learning methods of those from certain regions. The descriptive approach is a method of implementing community service. The team conducted a site survey and interviews with several residents’ representatives and coastal learners’ parents. The community service location is in Senggarang Village where foreign tourists pay a visit. The results of the community service are: (1) An increase in the knowledge and understanding of coastal learners about Grammar learning by using the Stepping the 5 Stairs "A" technique, (2) Coastal learners’the motivation to continue learning Grammar, and (3) There are requests from coastal learners, parents, RT, RW, and Karang Taruna Senggarang to the team to continue similar activities going forward